3- Mise en scène de la mort dans les manifestations de grèves au Gabon - Etoughé-Efé, Jean-Emery (African Sociological Review, 2021)
Corporate and/or wage claims are at the centre of conflicts between employers and employees. They can be expressed in the form of strikes. These are work-related struggles that are part of conflicting social relationships and govern today’s societies. From this point of view, work is always at the heart of conflicts in modern societies. Defined as the collective and concerted cessation of work to support professional demands, the strike remains quite strongly associated, in its current representations, with a work stoppage, more or less long. Reports in Gabon reveal that in public administrations and in private companies, expressions of strike show a certain evolution in their manifestations. Some strike practices are inspired by symbols associated with funeral rituals, which denotes the vindictive nature of these demonstrations.